Weathering the Storm : Responses by Cambodian Firms to the Global Financial Crisis - Guimbert, Stephane; Oostendorp, Remco (World Bank, Washington, DC, 2013)
Firms have various ways to cope with external risks. This paper analyzes the risk coping behavior that entails the smoothing of inputs (labor, raw materials, or capital). The theoretical framework shows that, if they face adjustment costs, firms prefer to smooth their inputs, especially if they expect a demand shock to be temporary. However, credit constrained firms will be adversely affected by the presence of liquidity constraints, and this will create a welfare loss due to incomplete smoothing. The authors estimate this behavior using a panel of Cambodian firms at the time of the 2008 global economic crisis. The survey shows that these firms were hard hit by the economic crisis between 2008 and 2009, with an average fall in demand (sales) of 30 percent. Based on the theoretical framework, the analysis can estimate the responsiveness of labor, capital, and raw materials input demand to demand shocks. It finds that firms try to smooth in particular if they believe the shock is temporary; in fact non-credit constrained firms reduce their inputs much less than firms that were credit constrained when the demand shock is expected to be temporary. The paper estimates that the welfare loss from incomplete smoothing due to credit constraints is many multiples of the adjustment costs of the firms that were not credit constrained. This has important policy implications about the role of financial sector development and regulations beyond the capital market. This micro analysis also has macro implications: if all firms expect a shock to be permanent, their combined limited smoothing of inputs will indeed make the shock more likely to be permanent.